Effect of antioxidants on kidney damage repair in - diabetes-induced animal: a literature study - Astri Pradini; Dian Anggraeny; Tatang Bisri; Diana Akmalia (ACTA Medical Health Sciences, 2023)
Diabetes mellitus is a disease characterized by hyperglycemia. Chronic hyperglycemia indiabetes mellitus can cause various complications, one of which is diabetic nephropathy,which affects the kidney. Chronic hyperglycemia causes an increase in free radicals and adecrease in antioxidant activity resulting in oxidative stress conditions. This study aims to determine kidney damage caused by oxidative stress and the role of antioxidants in reducingthis damage through literature studies. The literature used comes from Google search results such as PubMed, Google Scholar, ResearchGate, and ScienceDirect. From the search results, ten journals meeting the inclusion and exclusion criteria were selected for review and comparison so that a conclusion could be drawn. The results of this literature study have demonstrated that biochemical parameters, such as increased levels of creatinine, urea, malondialdehyde (MDA), and decreased antioxidant enzymes, as well as kidney histological parameters, such as changes in the shape of tubules, glomeruli, and increased kidney expression, are indicators of kidney damage caused by oxidative stress. The mechanism of antioxidants in reducing kidney damage is through DNA cutting, binding to phenolic OH groups, down-regulation of the oxidase expression of nitrogen oxides 4 nicotinamide adenine dinucleotide phosphate (Nox4 NADPH), antioxidant enzyme systems, activation of the activated protein kinase pathway - silent mating type information regulation 2 homolog 1- peroxisome proliferator-activated receptor-γ coactivator 1α (AMPK-SirT1- PGC-1 α), protein glycation reactions, and inhibition of protein 53 (P53) so that erythroid nuclear factor 2-related factor 2 (Nrf2) can activate antioxidant gene transcription. DOI : 10.35990/amhs.v2n1.p46-53 REFERENCE Widjaja SS, Rusdiana. Extract ethanol of Poguntano in alloxan-induced diabetic rats. Bangladesh J Med Sci. 2018;17(2):251–4. Shaw JE, Sicree RA, Zimmet PZ. Global estimates of the prevalence of diabetes for 2010 and 2030. Diabetes Res Clin Pract. 2010;87(1):4–14. Infodatin tetap produktif, cegah, dan atasi Diabetes Melitus 2020 [Internet]. Pusat Data dan Informasi Kementrian Kesehatan RI. 2020. p. 1–10. Available from: https://pusdatin.kemkes.go.id/resources/download/pusdatin/infodatin/Infodatin-2020-Diabetes-Melitus.pdf Adrian A, Fathonah S, Amatiria G. Pengaruh ultra filtration rate (UFR) terhadap kadar gula darah dan tekanan darah pada pasien DM dengan komplikasi CKD yang menjalani hemodialisis. J Keperawatan. 2014;10(1):81–9. Atmaharmoni W, Soeng S, Evacuasiany E. Gambaran pasien rawat inap diabetic kidney disease di Rumah Sakit Immanuel Bandung. J Kedokt Maranatha. 2012;11(2):140–7. Firdaus M, Chamidah A, Nurcholis AR, Yulaikah S, Anggraeni PY, Suryanata WA, et al. Effect of Sargassum polycystum extract on liver and kidney of diabetic rats. Pharmaciana. 2017;7(2):195–204. Bolignano D, Cernaro V, Gembillo G, Baggetta R, Buemi M, D’Arrigo G. Antioxidant agents for delaying diabetic kidney disease progression: A systematic review and meta-analysis. PLoS One. 2017;12(6):1–16. Jawi IM, Sumardika IW, Linawati NM. Pencegahan gangguan fungsi ginjal karena stres oksidatif pada tikus diabetes dengan ubi jalar ungu. J Vet. 2014;15(2):274–80. Sureshbabu A, Ryter SW, Choi ME. Oxidative stress and autophagy: Crucial modulators of kidney injury. Redox Biol. 2015;4:208–14. Available from: http://dx.doi.org/10.1016/j.redox.2015.01.001 Rohmatussolihat P, Si S. Antioksidan, penyelamat sel-sel tubuh manusia. BioTrends. 2009;4(1):5–9. Nasri H. Protective effects of herbal antioxidants on diabetic kidney disease. J Res Med Sci. 2014;82–3. Prawitasari DS. Diabetes melitus dan antioksidan. J Kesehat dan Kedokt. 2019;1(1):47–51. Available from: https://doi.org/10.24123/kesdok.v1i1.249613 Septiana AT, Asnani A. Aktivitas antioksidan ekstrak rumput laut Sargassum duplicatum. J Teknol Pertan. 2013;14(2):79–86. Bao L, Cai X, Dai X, Ding Y, Jiang Y, Li Y, et al. Grapeseed proanthocyanidin extract ameliorates podocyte injury by activating peroxisome proliferator-activated receptor-γ coactivator 1α in low-dose streptozotocin- and high-carbohydrate/high-fat diet-induced diabetic rats. Food Funct. 2014;5(8):1872–80. Available from: http://dx.doi.org/10.1039/C4FO00340C Wang L, Wu CG, Fang CQ, Gao J, Liu YZ, Chen Y, et al. The protective effect of α-lipoic acid on mitochondria in the kidney of diabetic rats. Int J Clin Exp Med. 2013;6(2):90–7. Liu IM, Tzeng TF, Liou SS, Chang CJ. Beneficial effect of traditional Chinese medicinal formula Danggui-Shaoyao-San on advanced glycation end-product-mediated renal injury in streptozotocin-diabetic rats. Evidence-based Complement Altern Med. 2012;2012. Wahyuni AS, Munawaroh R. Potensi ekstrak etanol beras hitam sebagai penurun gula darah pada tikus nefropati diabetes. Univ Res Coloquium. 2015;58–63. Tandi J, Wulandari A, Asrifa. Efek ekstrak etanol daun gendola merah (Basella alba L.) terhadap kadar kreatinin. Galen J Pharm. 2017;3(2):93–102. Available from: http://jurnal.untad.ac.id/jurnal/index.php/Galenika/index Gargouri M, Hamed H, Akrouti A, Dauvergne X, Magné C, El Feki A. Effects of Spirulina platensis on lipid peroxidation, antioxidant defenses, and tissue damage in kidney of alloxan-induced diabetic rats. Appl Physiol Nutr Metab. 2018;43(4):345–54. Yoon SP, Maeng YH, Hong R, Lee BR, Kim CG, Kim HL, et al. Protective effects of epigallocatechin gallate (EGCG) on streptozotocin-induced diabetic nephropathy in mice. Acta Histochem. 2014;116(8):1210–5. Available from: http://dx.doi.org/10.1016/j.acthis.2014.07.003 Guo W, Tian D, Jia Y, Huang W, Jiang M, Wang J, et al. MDM2 controls NRF2 antioxidant activity in prevention of diabetic kidney disease. Biochim Biophys Acta–Mol Cell Res. 2018;1865(8):1034–45. Available from: https://doi.org/10.1016/j.bbamcr.2018.04.011 Peng X, Su H, Liang D, Li J, Ting WJ, Liao SC, et al. Ramipril and resveratrol co-treatment attenuates RhoA/ROCK pathway-regulated early-stage diabetic nephropathy-associated glomerulosclerosis in streptozotocin-induced diabetic rats. Environ Toxicol. 2019;34(7):861–8. Mahmoodnia L, Aghadavod E, Beigrezaei S, Rafieian-Kopaei M. An update on diabetic kidney disease, oxidative stress, and antioxidant agents. J Ren Inj Prev. 2017;6(2):153–7. Available from: http://dx.doi.org/10.15171/jrip.2017.3024 Gluhovschi C, Gluhovschi G, Petrica L, Timar R, Velciov S, Ionita I, et al. Urinary biomarkers in the assessment of early diabetic nephropathy. J Diabetes Res. 2016;1–13. Aghadavod E, Khodadadi S, Baradaran A, Nasri P, Bahmani M, Rafieian-Kopaei M. Role of oxidative stress and inflammatory factors in diabetic kidney disease. Iran J Kidney Dis. 2016;10(6):337–43. Khidir KA, Kareem SR, Kakey IS. Role of green tea extract in reducing pathological changes of induced diabetes mellitus in rats. Rafidain J Sci. 2013;24(4):1–12.